Pragmatic Functions of Questions Found in the TV Series The Office - Tiffani Rizki Putri Baihaqi; Tofan Dwi Hardjanto (Universitas Gadjah Mada, 2020)
Questions are always present in people’s lives as they are used in daily conversation, not only as a tool to initiate a conversation but also to keep that conversation alive and at the same time to gain information from the interlocutor. This research aims to investigate the syntactic forms of questions and their pragmatic functions found in a TV series entitled The Office Season 1 as the data source. The data used in the research were interrogative utterances, their answers, and the context of the conversation. The results show that 409 questions were found, consisting of 214 (52%) yes/no questions and 195 (48%) WH questions. What outnumbers the other question words with a total of 117 (60%) questions. These questions were used to serve 27 pragmatics functions, seeking the most frequent function, amounting to 140 questions or 34% of the whole data. The dominant use of the questions word what and the function seeking information might be due to the setting of the place where the conversation is held, that is, The Office.